2023
DOI: 10.3354/esr01237
|View full text |Cite
|
Sign up to set email alerts
|

Recent decline of green turtle Chelonia mydas nesting trend at Tortuguero, Costa Rica

Abstract: Trends in abundance of different life stages present important opportunities to manage the conservation of threatened species. For marine turtles, most trend assessments are based on long-term monitoring of nesting aggregations, which provides critical information on rookery dynamics across years. Tortuguero, Costa Rica, is the largest nesting colony of the green turtle Chelonia mydas in the Atlantic. Here we present an updated trend in annual clutch abundance spanning over 50 yr of monitoring at Tortuguero. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Despite historically facing intense exploitation (Ferreira‐Airaud et al, 2022 ), both green and hawksbill turtle populations nesting in São Tomé are showing a progressive trend, reflecting recovery patterns observed in other rookeries (Barbosa et al, 2018 ; Blumenthal et al, 2021 ; Hudgins et al, 2023 ; Kauffman, 2022 ; Mazaris et al, 2017 ; Restrepo et al, 2023 ; Santos et al, 2013 ; Seminoff et al, 2015 ). The encouraging positive trends observed in both species are indicative of the substantial impact of conservation efforts implemented in the region in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite historically facing intense exploitation (Ferreira‐Airaud et al, 2022 ), both green and hawksbill turtle populations nesting in São Tomé are showing a progressive trend, reflecting recovery patterns observed in other rookeries (Barbosa et al, 2018 ; Blumenthal et al, 2021 ; Hudgins et al, 2023 ; Kauffman, 2022 ; Mazaris et al, 2017 ; Restrepo et al, 2023 ; Santos et al, 2013 ; Seminoff et al, 2015 ). The encouraging positive trends observed in both species are indicative of the substantial impact of conservation efforts implemented in the region in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these taxa face significant reductions in their population numbers and are at risk of extinction (Butchart et al, 2010;Dulvy et al, 2021;Mortimer & Donnelly, 2008;Pimiento et al, 2020;Restrepo et al, 2023;Wallace et al, 2011), requiring ocean governance with conservation measures (Dulvy et al, 2021;Pimiento et al, 2020) that range from intergovernmental agreements to national and local conservation programs, including protected areas (Duda, 2016;Huang et al, 2022;Lotze, 2021;Maestro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, from another perspective, these data provide a baseline for one of the most significant remaining forging areas for green sea turtles and one that is closely connected to one of the world’s largest breeding sites [ 113 ]. Understanding the geographical origins and connections between breeding sites and populations using different foraging areas is critical for conservation management and modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of the illegal harvesting rates from these projects found that illegal take at each of these sites is declining because of conservation efforts. Despite this, these beaches continue to lose adult turtles and nests to illegal harvesters every season, and this population of green (Chelonia mydas) turtles is in decline (Pheasey et al 2021, Restrepo et al 2023.…”
Section: Introductionmentioning
confidence: 99%